Monocyte count combined with GTVnx is an independent prognostic factor in non-metastatic nasopharyngeal carcinoma receiving radiotherapy - Yang, Li-Na; Song, Yun-Rui; Zhang, Huan; Tu, Hong-Lei; Lu, Ming-Yue; Liu, De-Qing; Sui, Jiang-Dong; Li, Dan; Xie, Yue; Wang, Ying (Frontiers in Oncology, 2025)
Background and purposeThe relationship between peripheral blood monocyte count and primary gross tumor volume with survival prognosis in newly diagnosed nasopharyngeal carcinoma(NPC) patients who received radiotherapy remains unclear. Therefore, We conducted a cohort study to assess the association of peripheral blood monocyte count and primary gross tumor volume with survival outcomes in newly diagnosed non-metastatic NPC patients who received radiotherapy.Materials/methodsWe included newly diagnosed non-metastatic NPC patients who underwent radiotherapy in our hospital from January 2013 to December 2015. General clinical characteristics such as age, gender, ECOG score and tumor stage, peripheral blood monocyte count, lymphocyte count, white blood cell count (WBC), neutrophil count, radiotherapy technology, total radiotherapy days, gross tumor volume of nasopharyngeal carcinoma (GTVnx) and gross tumor volume of cervix node (GTVnd) of patients before radiotherapy, and whether chemotherapy was induced were recorded. The primary endpoint was overall survival, the secondary endpoint was progression-free survival. Univariate and multivariate COX regression were used to analyze the relationship among peripheral blood monocyte count, GTVnx, and survival outcomes. Spearman correlation analysis was used to analyze the correlation between risk factors. Based on the independent risk factors for OS, we further divide patients into three different risk groups, and the differences in clinical and therapeutic indicators and survival outcomes between the three groups were analyzed using a one-way analysis of variance.ResultsA total of 448 participants were included in the study, the median follow-up time was 74.3 months. Of these, 97 (21.7%) died. In the univariate and multivariate Cox regression analyses, peripheral blood monocyte count and GTVnx were independently associated with OS. The high monocyte count and GTVnx were associated with the poor OS and PFS. Correlation analysis showed that monocyte count was positively correlated with WBC, platelet, and neutrophil. GTVnx was positively correlated with platelet, neutrophil, and Epstein-Barr virus before treatment. Survival curves significantly differed among patients in different risk groups for OS (p = 0.0008) and PFS (p = 0.0007). Besides, For every increase in monocyte unit count, the OS and PFS risks of patients in the low GTVnx group increased by 2.64 and 2.31 folds, respectively.ConclusionsPeripheral blood monocyte count combined with GTVnx is an independent predictor for overall survival and progression free-survival in newly diagnosed non-metastatic NPC patients who received radiotherapy. The benefit of patients with GTVnx< 28.5cm3 could be remarkably attenuated by the high monocyte count.